Digital Storytelling for Social Justice: Empowering Students to Address Inequality through Creative Narratives - Moh. Imron Rosidi; Ismaul Fitroh; Samavia Zia (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study investigates the use of digital storytelling (DST) as an educational strategy to enhance students’ critical thinking, empathy, and social awareness, particularly in addressing social injustice issues. Despite the growing emphasis on social justice education, traditional teaching methods often fail to engage students meaningfully or to connect personal experiences with broader societal contexts. This research aims to explore how DST can foster reflective learning, empathy, and social responsibility among students. A qualitative methodology was employed, involving data collection through student-created narratives, content analysis using ATLAS.ti, and thematic coding to identify recurring patterns and insights. The findings reveal that DST significantly improves students’ critical thinking skills and emotional engagement, allowing them to articulate personal experiences while understanding social structures and injustices. Students demonstrated increased empathy and the ability to link creative narratives with real-world social issues. Comparative analysis indicates that DST offers advantages over conventional pedagogical methods by promoting interactive, reflective, and socially conscious learning. The study concludes that integrating digital storytelling into educational practices can effectively cultivate socially aware, empathetic, and creative learners, thereby contributing to a more just and inclusive educational environment.